История государства Российского: жизнеописания : XX век (сост.: С. Н. Синегубов, П. Л. Вахтина, А. В. Шевцов) - Синегубов С. Н. (2000)
Экземпляры: (20170918) / Инвентарный номер: 2109 / Цена: / Сис.шифр: 63.3(2) / Авт.знак: И 90 / ББК: 63.3(2)